REITERATIONS IN 'PRIANGAN SI JELITA' AND THEIR IMPLICATIONS TOWARD INDONESIAN LANGUAGE LEARNING AT SECONDARY SCHOOLS (REITERASI DALAM 'PRIANGAN SI JELITA' DAN IMPLIKASINYA PADA PEMBELAJARAN BAHASA INDONESIA DI SMP) - Asep Muhyidin (Leksema: Jurnal Bahasa dan Sastra, 2018)
This research studied the use of reiterationÂ  in che ollection of poems Priangan Si Jelita. The object of this research is reiteration which consist of repetition, synonymy, metonymy, and hyponymy. This research used both theoretical and methodological approaches. The former was discourse analysis whereas the latter was qualitative-descriptive approach. The result of analysis shows that the strength and beauty of the forms and meanings of the poems in Priangan Si Jelita are mostly built by the lexical cohesive elements within, particularly reiteration covering repetition, synonymy, metonymy, and hyponymy. The most dominant reiteration in the poems is repetition. This research has an implication toward Indonesian language learning for class IXÂ  students of junior high school in the material of paraphrasing poems in accordance with the structure and principles of texts in written form